Sustainability Discourse Analysis Using the AIDA Model in Le Minerale’s Brand Communication - Jacobus Rico Kuntag; Survey Sijabat; Dodhy Hyronimus Ama Longgy; Evelin Giovani (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Sustainability discourse has become a key component of brand communication in the bottled water industry, where environmental responsibility is often used to legitimise consumption. Through packaging, advertising, and digital media, brands construct images of purity, safety, and ecological care, even though consumers may not critically assess such claims. This study analyses how Le Minerale’s sustainability communication is constructed and how these messages are understood and trusted by consumers in Merauke. Using Critical Discourse Analysis based on Fairclough’s three-dimensional framework integrated with the AIDA model, this study examines textual and visual elements from packaging, the official website, and video advertisements, supported by a consumer survey. The findings show that sustainability is constructed through natural imagery, claims of mountain water purity, and recyclable packaging technology. Across the AIDA stages, consumer responses are shaped through symbolic and moral appeals. Survey results indicate that consumers generally trust these sustainability claims, despite limited understanding of technical terms. This suggests that sustainability discourse primarily functions as a marker of moral and social identity rather than as substantive environmental education.